1993
DOI: 10.1002/j.1460-2075.1993.tb05970.x
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced localized Ca2+ spikes directly triggering exocytotic secretion in exocrine pancreas.

Abstract: We investigated how agonist-induced patterned rises in cytosolic Ca2+ concentration ([Ca2+] while acetylcholine (ACh) always triggered primary Ca2+ spikes at the granular area which bears secretory granules. Secretion was monitored by measuring capacitance with the patch clamp method. Errors in the estimates of membrane capacitance (C) due to changes in conductance (G) were experimentally as well as theoretically evaluated to be one-tenth of the actual signals. We found that A23187 raised G without chang C a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
72
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(78 citation statements)
references
References 28 publications
5
72
1
Order By: Relevance
“…In some cases little or no [Ca 2ϩ ] i increase at all is observed in basolateral regions (5,6). This spatial pattern of [Ca 2ϩ ] i signaling has been suggested to be important for both unidirectional fluid secretion (2, 7) and exocytosis (8).…”
mentioning
confidence: 82%
“…In some cases little or no [Ca 2ϩ ] i increase at all is observed in basolateral regions (5,6). This spatial pattern of [Ca 2ϩ ] i signaling has been suggested to be important for both unidirectional fluid secretion (2, 7) and exocytosis (8).…”
mentioning
confidence: 82%
“…In pancreatic acinar cells, C m measurements have been used to demonstrate that application of a cholinergic agonist or artificial Ca 2ϩ elevation can induce changes in cell surface area (8,15,16,22). In the current study we determined whether this technique could be used to monitor membrane surface dynamics of parotid acinar cells.…”
Section: Exocytosis Induced By Camp and Camentioning
confidence: 99%
“…A wide range of epithelial functions such as fluid and electrolyte secretion (Kasai and Augustine, 1990;Ito et al, 1997), exocytosis (Maruyama et al, 1993;Ito et al, 1997) or TJ permeability (Nathanson et al, 1992) are regulated by cytosolic Ca 2+ . Videoimaging of Ca 2+ indicators have demonstrated that, in a large number of epithelial cells, Ca 2+ signals are remarkably organized in space and often polarized.…”
Section: Introductionmentioning
confidence: 99%